Perkembangan LKPD Berbasis Gambar untuk Meningkatkan Keterampilan Generic Sains - Hasanah, Nurdina; Elza, Nanda; Aisyah Hrp, Siti; Nabila, Hanny; Anas, Nirwana (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to determine the effect of the use of image-based worksheets on the learning process material. This research is research and development. So that we can know the process of this LKPD towards students' critical thinking. This research is used to produce certain products and test the effectiveness of these products. This study aims to develop a product in the form of Student Activity Sheets (LKPD), to know the attractiveness of image-based LKPD, and to determine the effectiveness of LKPD in improving student learning outcomes Abstract provides an overview of the research carried out, written in full and clear. Keywords: abstract, bold, italic